Engineering transcriptional regulatory networks for improving second-generation fuel ethanol production in Saccharomyces cerevisiae - Dongming Sun; Longhao Wu; Xiaocong Lu; Chenhao Li; Lili Xu; Hongxing Li; Deyun He; Aiqun Yu; Tao Yu; Jianzhi Zhao; Hongting Tang; Xiaoming Bao (Synthetic and Systems Biotechnology)
Presently, Saccharomyces cerevisiae demonstrates proficient co-fermentation of glucose and xylose, marking a significant advancement in second-generation fuel ethanol production. However, the presence of high concentrations of inhibitors in industrial lignocellulose hydrolysates and post-glucose effect caused by glucose consumption hinders severely impedes yeast robustness and xylose utilization for ethanol fermentation. Even worse, the antagonism between xylose utilization ability and strain robustness was observed, which proposes a difficult challenge in the production of second-generation fuel ethanol by S. cerevisiae. This review introduces the effect of engineering transcriptional regulatory networks on enhancing xylose utilization, improving strain robustness, alleviating antagonism between xylose utilization and strain robustness, and reducing post-glucose effect. Additionally, we provide an outlook on the developmental trends in this field, offering insights into future directions for increasing the production of second-generation fuel ethanol in S. cerevisiae.